A low cost field‐survey method for mapping seagrasses and their potential threats: an example from the northern Gulf of Aqaba, Red Sea. Issue 2 (19th August 2016) - Winters, Gidon; Edelist, Dor; Shem‐Tov, Rachamim; Beer, Sven; Rilov, Gil
Abstract: 1. In the Gulf of Aqaba (GoA), coral reefs are considered the dominating ecosystem, while seagrass meadows, recognized worldwide as important ecosystems, have received little attention. Absence of comprehensive seagrass maps limits awareness, evaluations of associated ecosystem services, and implementation of conservation and management tools. 2. Presented here are the first detailed maps of seagrass meadows along the Israeli coast of the northern GoA. Mapping was performed by snorkelling along transects perpendicular to the shore above meadows growing at 15–25 m. Measurements along these transects included position, meadow depth and visual estimations of seagrass cover. Shallow boundaries of meadows, parallel to shore, were recorded by GPS tracking. Supplementary work included drop‐camera boat surveys to determine the position of the deeper edge of meadows. In addition, GIS layers were created that indicated shoreline infrastructures, near‐shore human activities and potential pollution threats. Ecosystem services of seagrass meadows mapped were valuated using a benefit transfer approach. 3. In total, 9.7 km of the 11 km shoreline were surveyed and 2830 data points collected. Seagrasses were growing along 7.5 km of the shoreline, with shallow (15–25 m) meadows found to cover an area of 707 000 m 2 and valued at more than US$ 2 000 000 yr ‐1 in associated ecosystem services. Pilot drop‐camera surveys (additional 283 data points) indicated that meadows can extend down to 50 m in some places. Coastal uses and threats varied in character and location. A municipality runoff point and drainage canal located close to the largest meadow were identified as the main threats to local seagrasses. 4. These low‐cost methods enhance our understanding of seagrass distribution in the northern GoA. They demonstrate a GIS‐based tool for assessing how environmental changes might affect the cover and state of seagrasses, improving efforts to conserve seagrass, and have particular relevance to seagrass mapping in developing countries and/or island nations. Copyright © 2016 John Wiley & Sons, Ltd.